PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAPKINERJA MELALUI MOTIVASI KERJA - PARLIS SINAGA (STIE Indonesia Malang, 2018)
The objective of this research is to analyze the effect of organizational culture and compensation to performance employe by motivation of axaIndonesia Jakarta. In this research data collection use the questioner spread to respondents. The sampling method collection used in this research is non-probability sampling, with collection technique is purposive sampling. Total sample of this research is 210 respondences. The analysis used in this research is Structural Equation Modelling (SEM) analysis technique, method for hypothesis testing using software LISREL. The results of this research show that organizational culture has no significant impact to motivation, and organizational has no significant impact to performance employee. Compensation has a significant effect on work motivation, compensation has a significant effect on employee performance and work motivation has a significant effect on employee performance.Keywords: Organizational culture, compensation, performance employee and work motivation.